TINJAUAN PENGODEAN KLINIS PASIEN BPJS GUNA MENDUKUNG KETEPATAN GRUPING INA-CBG’S DI RUMAH SAKIT CIMAHI - Imelda Retna Weningsih; FX.Kusna Arintaka (Jurnal Kesehatan, 2022)
This research was motivated when the authors conducted a coding review of 30 medical record samples. The results were 33.33% incorrect in clinical coding. The purpose of this paper is to get an overview of the clinical coding of BPJS patients to support the accuracy of grouping in the INA-CBG's system at Cimahi Hospital. This type of research is descriptive quantitative, with a population of 783 medical records with 88 medical records of samples. There was 34,09% inaccuracy, based on the ICD-10 rules set by Cimahi Hospital. The reason was the wrong choice of selection of the Main Diagnosis, and the officers did not look back at the Minister of Health Regulation 76/2016, and as well as the Minutes of Agreement. Another factor that affects the inaccuracy of coding is that the coder does not see the contents of the medical record as a whole (abstraction process), and there is no controlling activity or supervision of clinical coding specifically for BPJS patients. The results of the INA-CBGs grouper were 25% different. Concluded that the clinical coding activity of BPJS patients had not followed the standard ICD-10 rules and adjusted PMK 76/2016 and the Minutes of Agreement because the results had an impact on grouping or grouping INA-CBGs. Suggested that periodic coding audits should be carried out, and holding regular meetings to review coding activities according to government policy